2023
DOI: 10.3390/molecules28135150
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Antioxidant/Antiradical Effects and In Vitro Intestinal Permeation of Oleocanthal and Its Metabolites Tyrosol and Oleocanthalic Acid

Abstract: (1) Background: In recent years, numerous studies have highlighted the beneficial effects of extra virgin olive oil (EVOO) as an active ingredient against chronic diseases. The properties of EVOO are due to its peculiar composition, mainly to its rich content of polyphenols. In fact, polyphenols may contribute to counteract oxidative stress, which often accompanies chronic diseases. In this work, the antioxidant effects of high-value polyphenol oleocanthal (OC) and its main metabolites, tyrosol (Tyr) and oleoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…The antioxidant properties of hydroxytyrosol arise from its capacity to function as a potent scavenger of free radicals [44][45][46], its chelating effect on metals-diminishing the production of ROS from derived reactions [47]-and its ability to stimulate various antioxidant systems by promoting the activity of enzymes like catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GPx) [48][49][50][51], or by activating the transcription factor Nrf2 [52,53]. Additionally, (-)-oleocanthal and (-)-oleacein, while not as well studied as hydroxytyrosol for their antioxidant properties, have been shown to act as free radical scavengers [54][55][56].…”
Section: Ht Alkyl Ethersmentioning
confidence: 99%
“…The antioxidant properties of hydroxytyrosol arise from its capacity to function as a potent scavenger of free radicals [44][45][46], its chelating effect on metals-diminishing the production of ROS from derived reactions [47]-and its ability to stimulate various antioxidant systems by promoting the activity of enzymes like catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GPx) [48][49][50][51], or by activating the transcription factor Nrf2 [52,53]. Additionally, (-)-oleocanthal and (-)-oleacein, while not as well studied as hydroxytyrosol for their antioxidant properties, have been shown to act as free radical scavengers [54][55][56].…”
Section: Ht Alkyl Ethersmentioning
confidence: 99%
“…The content of total phenols-expressed as gallic acid equival from 14.80 to 121.20 mg/100 g (mean value: 53.72 mg/100 g) and was mainl to deacetoxyligstroside aglycone, oleuropein aglycone, deacetoxyoleurop and ligstroside aglycone. Trolox equivalent antioxidant capacity (TEAC) a stability were both positively correlated with the phenolic content [26 published study conducted by Cuffaro et al [27] investigated the antioxidan high-value polyphenol oleocanthal and its main metabolites (tyrosol and acid) in terms of scavenging capacity towards biologically relevant rea…”
Section: Antioxidant and Anti-inflammatory Properties Of Oleocanthalmentioning
confidence: 99%
“…Trolox equivalent antioxidant capacity (TEAC) and oxidative stability were both positively correlated with the phenolic content [26]. A recently published study conducted by Cuffaro et al [27] investigated the antioxidant effects of the high-value polyphenol oleocanthal and its main metabolites (tyrosol and oleocanthalic acid) in terms of scavenging capacity towards biologically relevant reactive oxygen species (ROS). Remarkably, authors demonstrated that oleocanthal and tyrosol act as ROS scavengers, with a pronounced scavenging capacity towards superoxide anion radical (O2 •− ) and hypochlorous acid (HOCl) [27].…”
Section: Antioxidant and Anti-inflammatory Properties Of Oleocanthalmentioning
confidence: 99%
See 1 more Smart Citation
“…Olives and olive-derived products are valuable sources of natural polyphenols, such as secoiridoids (oleocanthal, oleacein), simple phenols (tyrosol and hydroxytyrosol), flavonoids, and lignans. Secoiridoids are the prominent polyphenols present in olive oil, possessing numerous pharmacological properties and conferring the bitterness, pungency, and astringency of olive oil [14][15][16][17][18]. Within its bioactive compounds, olive oil contains lignans, which are the most recently identified phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%